Tinig at kapangyarihan mga kuwentong buhay ng mga kababaihang manggagawa sa bahay - Ofreneo, Rosalinda Pineda (Quezon City University of the Philippines Press, 1999)
Research on women working in small-scale industries in the Philippines.
Includes bibliographical references (pages 178-183)
In Tagalog.
Keywords: Home labor -- Philippines; Home-based businesses -- Philippines; Subcontracting -- Philippines; Women -- Employment -- Philippines